Digital libraries: a catalyst to the changing process of accessing and use of information in academic community - Vrana, Radovan (Array, 2000)
The aim of this paper is to introduce digital libraries as a new form of information resource supporting faster creation, collection, processing, organization and use of high quality information and knowledge and serving as a means of communication in the academic community. The foundation of this type of communication is information technology which helped the advancement in development of libraries presenting us a new category of libraries: digital libraries. During the last decade most of the existing digital libraries have been developed as a part of different scientific projects having significant impact on scientific communication while changing its paradigms at the same time. Having strong foundations in IT, digital libraries can further advance communication within the system of higher education making it more competitive and thus resulting in further advancement in the development of the basic information infrastructure and content creation. Digital libraries already have great impact in making electronic information more available to the academic staff and students by letting them being involved in various ongoing international and interdisciplinary projects. As an outcome, digital libraries are becoming technical and organizational centers for interinstitutional cooperation in projects thus engaging technology, financial means, human resources in formation of new communication paradigms and creation of national strategies of development of new information resources.